Female hormone therapy and risk of intracranial hemorrhage and focal neurological deficits in patients with cavernous malformations of the central nervous system - Wildi, Saskia; Nager, Selina; Staartjes, Victor; Stumpo, Vittorio; Özkaratufan, Sena; Krayenbühl, Niklaus; Bozinov, Oliver; Regli, Luca; Velz, Julia (Frontiers in Neurology, 2025)
BackgroundFemale hormone therapy [FHT, birth control treatment and postmenopausal hormone replacement therapy (HRT)] is not withheld from patients with cerebral cavernous malformations (CCM), notwithstanding the uncertainty surrounding the impact of these medications on the risk of intracranial hemorrhage (ICH). This study aimed to evaluate the impact of female hormone therapy on the risk of ICH or focal neurological deficit (FND) in patients with CCM.MethodsThe prospective institutional database was examined for all patients with CCM treated at our institution between 2006 and 2023. Inclusion criteria comprised patients with confirmed CCM diagnosis through radiological and/or histological examination, availability of baseline clinical characteristics, accessible medication history, and follow-up data. Patients were stratified based on their medical treatment regimen, which included female hormone therapy or no treatment. The study assessed the time-to-event probability and the number of events (ICH or FND) during the follow-up period.ResultsA total of 328 female patients with CCM were included in the final analysis. Among them, 56 patients (17.1%) were receiving female hormone therapy. Specifically, 37 patients (11.3%) were using birth control treatments and 19 patients (5.8%) were on HRT. The mean number of ICH per patient was 0.43 (SD 1.11) in the FHT group and 0.38 (SD 0.8) in the control group (p = 0.1), while the mean number of FND was 0.36 (SD 0.84) in the FHT group and 0.28 (SD 0.66) in the control group (p = 0.58). The time to first ICH was 1631.5 days (SD 2324.6) in the FHT group and 1161.4 days (SD 1650.8) in the control group (p = 0.35), while the time to first FND was 1601.0 days (SD 1934.1) in the FHT group and 1208.1 days (SD 1649.5) in the control group (p = 0.86).ConclusionThe study shows that female patients with a diagnosis of cerebral cavernous malformation receiving female hormone therapy do not experience a significant higher likelihood of intracranial hemorrhage or focal neurological deficit. These findings indicate that, despite the observed tendency, female hormone therapy does not significantly alter the risk of these events in the observed female patients.